PARIWARA POLITIK DI TELEVISI MENYONGSONG PEMILU LEGISLATIF 2009 - Hadi, Aulia (P2KK LIPI, 2010)
The development of television political ads in Indonesia has been increased significantly since the first use in the election of 1999. Through television political ads, political parties have greater freedom to express their interest rather than media news coverage. Moreover, television could cover wider area than other mass media. Because of those reasons, political parties spend a lot of their budgets for television political ads. The number and modes of television political ads have increased significantly than before. This paper tries to describe how political parties represent themselves in television ads. It will be analyzed from verbal and non-verbal content of television political ads. This article argues that television ads have been used to persuade rather than to provide political education to the audience. Keywords:political ads, television, political party (parpol), legislative election 2009 (Pileg 2009)